Effectiveness of dental whitening in patients with active fixed orthodontic treatment: A narrative review - Santillán-Guerra, Adrián Mauricio (2022)
Introduction: Currently dental aesthetics during fixed orthodontic treatment is an option required by patients, due to the frequent pigmentations that can occur in tooth enamel as a result of inadequate oral hygiene and plaque retention caused by fixed appliances. Objective: To determine the effectiveness of dental whitening and its side effects during active fixed orthodontic treatment, as an alternative aesthetic treatment in certain cases that merit it. Materials and methods: This narrative review evaluated 35 scientific articles from the Medline information sources (via PUBMED), EMBASE, SCOPUS, SCIELO, and LILACS from the last 10 years, published in Spanish, Portuguese, and English. We included 17 articles that met the selection criteria which were randomized clinical trials and observational studies, in vitro studies, and in vivo studies that evaluated in-office dental clearance, performed on patients using fixed orthodontic treatment at that time. Systematic reviews, case reports, and editorials were excluded. Results: It was observed that dental whitening in patients with active orthodontic treatment minimally affects the adhesion of the orthodontic apparatus to the tooth surface. In addition, some studies observed that the brackets interfere with the extension of the dental lightening, evidencing slightly darker areas. Conclusions: Dental whitening during orthodontic treatment can be given efficiently in clinical practice, depending on the aesthetic requirement of the patient. However, it is a recommended procedure in certain cases of great need for immediate aesthetics, since, the material with which the brackets are installed on the dental surface, will interfere with the extension of the lightening material, resulting in a darker shade in that sector and different from the surrounding tissue. Likewise, it will intervene in the adhesion to the dental surface, having many probabilities that the orthodontic apparatus can detach.